2019
DOI: 10.1021/acsabm.9b00680
|View full text |Cite
|
Sign up to set email alerts
|

Silica Release from Silane Cross-Linked Gelatin Based Hybrid Scaffold Affects Cell Proliferation

Abstract: Earlier, we had reported the synthesis and characterization of star-shaped poly­(d,l-lactide)-b-gelatin (ss-pLG) to improve cell adhesion and proliferation, but the stability of ss-pLG scaffolds remained a persistent issue. Here we show an increase in the stability of ss-pLG using 3-glycidoxypropyl trimethoxysilane (GPTMS) as a covalent cross-linker (h-ss-pLG). The rate of cell proliferation within Hep-G2 cultured h-ss-pLG scaffolds increased until the third day, and afterward it drastically declined. Further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
(93 reference statements)
1
18
0
Order By: Relevance
“…Gene expression was normalized to GAPDH. Fold change was calculated using the 2 –Δ Δ cq method as described earlier ( Balavigneswaran et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression was normalized to GAPDH. Fold change was calculated using the 2 –Δ Δ cq method as described earlier ( Balavigneswaran et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…This kind of scaffolds is biocompatible, and the porosity and mechanical strength can be controlled by the inorganic–organic coupling for being scaffolds on tissue engineering [ 87 , 88 ]. Moreover, the chemical crosslinking increases the hydrophobicity and thermal stability of these scaffolds [ 89 ]. The GPTMS hydrolysis at highly acid pH (H 2 SO 4 aqueous solution) and oxidation with NaIO 4 transform the epoxy into an aldehyde functionality, which forms a Schiff base with lysine residues at pH higher 10.1 (pK of the Lys).…”
Section: Mechanisms Of Silica/protein and Silica/polysaccharide Interactions And Their Impacts On The Functional Properties Of The Derivementioning
confidence: 99%
“…is kind of scaffolds is biocompatible, and the porosity and mechanical strength can be controlled by the inorganic-organic coupling for being scaffolds on tissue engineering [87,88]. Moreover, the chemical crosslinking increases the hydrophobicity and thermal stability of these scaffolds [89].…”
Section: Functionalization Of Protein or Polysaccharide Hydrogel Precursor With Silanesmentioning
confidence: 99%
“…to Gel could be due to the hydrophilicity of the polymer, as observed in the earlier reports published by our group and other authors. [23,33,36] It has been reported that up to 10% hemolysis is permissible for biomaterials. [54] Thus 0.…”
Section: Effects Of Ss-plg On Interaction With Bsamentioning
confidence: 99%
“…[22] Crosslinking the gelatin-grafted polymer with silane increased the hydrophobicity as well as the stability of scaffolds. [23] Studies have revealed that gelatin notably inhibits the formation of insulin amyloid fibrils. [24] Therefore, it is important to elucidate the biocompatibility of gelatin grafted poly(D,L-lactide) (PDLLA) and its effect on amyloid fibril formation to understand the potential of the synthetic polymers as anti-amyloidogenic agents.…”
Section: Introductionmentioning
confidence: 99%